Effects of Etching on Zircon Grains and Its Implications for the Fission Track Method - Tello Saenz, Carlos Alberto [UNESP]; Campos Curvo, Eduardo Augusto [UNESP]; Coelho Dias, Airton Natanael [UNESP]; Soares, Cleber Jose [UNESP]; Leopoldo Constantino, Carlos Jose [UNESP]; Alencar, Igor; Guedes, Sandro; Palissari, Rosane; Hadler Neto, Julio Cesar (Soc Applied Spectroscopy, 2012)
Studies of zircon grains using optical microscopy, micro-Raman spectroscopy, and scanning electron microscopy (SEM) have been carried out to characterize the surface of natural zircon as a function of etching time. According to the surface characteristics observed using an optical microscope after etching, the zircon grains were classified as: (i) homogeneous; (ii) anomalous, and (iii) hybrid. Micro-Raman results showed that, as etching time increases, the crystal lattice is slightly altered for homogeneous grains, it is completely damaged for anomalous grains, and it is altered in some areas for hybrid grains. The SEM (energy dispersive X-ray spectroscopy, EDS) results indicated that, independent of the grain types, where the crystallinity remains after etching, the chemical composition of zircon is approximately 33% SiO2:65% ZrO2 (standard natural zircon), and for areas where the grain does not have a crystalline structure, there are variations of ZrO2 and, mainly, SiO2. In addition, it is possible to observe a uniform surface density of fission tracks in grain areas where the determined crystal lattice and chemical composition are those of zircon. Regarding hybrid grains, we discuss whether the areas slightly altered by the chemical etching can be analyzed by the fission track method (FM) or not. Results of zircon fission track and U-Ph dating show that hybrid and homogeneous grains can be used for dating, and not only homogeneous grains. More than 50 sedimentary samples from the Bauru Basin (southeast Brazil) were analyzed and show that only a small amount of grains are homogeneous (10%), questioning the validity of the rest of the grains for thermo-chronological evolution studies using zircon FTM dating.
Keywords: Zircon; Micro-Raman spectroscopy; Fission track method; Scanning electron microscopy; SEM; Energy dispersive X-ray spectroscopy; EDS; Zircon crystal lattice; Zircon chemical etching